Image-based time series analysis to establish differential disease progression for two Fusarium head blight pathogens in oat spikelets with variable resistance - Pavicic, Mirko; Mouhu, Katriina; Hautsalo, Juho; Jacobson, Daniel; Jalli, Marja; Himanen, Kristiina (Frontiers in Plant Science, 2023)
Oat based value-added products have increased their favour as healthy foodstuff. Fusarium head blight (FHB) infections and the mycotoxins accumulated to the oat seeds, however, pose a challenge to oat production. The FHB infections are predicted to become more prevalent in the future changing climates, increasing the pressure for breeding new resistant cultivars. Till now, genetic links in oats against FHB infection have been difficult to identify. Therefore, there is a great need for more effective breeding efforts, including improved phenotyping methods allowing time series analysis of the disease progression. To these ends, dissected spikelets of several oat genotypes with different resistance profiles were studied by image-based methods during disease progression by Fusarium culmorum or langsethiae species. Chlorophyll fluorescence of each pixel in the spikelets was recorded after inoculation by the two Fusarium spp. and the progression of the infections were analysed by calculating the mean maximum quantum yield of PSII (Fv/Fm) values for each spikelet. The recorded values were i) the change in photosynthetically active area of the spikelet as percentage of its initial size, and ii) as a mean of Fv/Fm values of all fluorescent pixels per spikelets post inoculation, both indicative of the progression of the FHB disease. The disease progression was successfully monitored, and different stages of the infection could be defined along the time series. The data also confirmed the differential rate of disease progression by the two FHB causal agents. In addition, oat varieties with variable responses to the infections could be identified.